Rendimiento en ventas de la empresa INT FOOD SERVICES CORP (KFC) de la Ciudad de Babahoyo - Centro - Pazmiño Arteaga, Willian Fredy (2019)
The present case study was developed in the company KFC - Centro de Babahoyo with the purpose of determining the causes of why the sales yields have fallen in recent years. For the purposes of the case, the parameters of the explanatory research methodology were implemented, based not only on finding and describing the problems, but also on finding the causes that originate it. The results of the investigation were the following: excessive competition of substitute products, increase of new fast food restaurants in the town that affect sales, prices higher than the competition, the flyer and marketing plan is not having the expected effect, Little influx of customers daily at the store